2013
DOI: 10.1152/physrev.00011.2012
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Gated Proton Channels: Molecular Biology, Physiology, and Pathophysiology of the HVFamily

Abstract: Voltage-gated proton channels (HV) are unique, in part because the ion they conduct is unique. HV channels are perfectly selective for protons and have a very small unitary conductance, both arguably manifestations of the extremely low H+ concentration in physiological solutions. They open with membrane depolarization, but their voltage dependence is strongly regulated by the pH gradient across the membrane (ΔpH), with the result that in most species they normally conduct only outward current. The HV channel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
268
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 204 publications
(295 citation statements)
references
References 514 publications
(1,080 reference statements)
7
268
0
2
Order By: Relevance
“…We have carried out this exercise independent of the recently reported X-ray structure of the mHv1/CiVSD/GNC4 chimera. Due to the common overall architecture of VSDs, structural models for hHv1 have been constructed based on existing structures from either KvAP or Kv1.2 VSDs (3,6,20,24). We point out that given local sequence similarity, the recently determined VSD from Ci-VSP (CiVSD) represents a more logical and accurate structural template for hHv1 (16).…”
Section: Resultsmentioning
confidence: 99%
“…We have carried out this exercise independent of the recently reported X-ray structure of the mHv1/CiVSD/GNC4 chimera. Due to the common overall architecture of VSDs, structural models for hHv1 have been constructed based on existing structures from either KvAP or Kv1.2 VSDs (3,6,20,24). We point out that given local sequence similarity, the recently determined VSD from Ci-VSP (CiVSD) represents a more logical and accurate structural template for hHv1 (16).…”
Section: Resultsmentioning
confidence: 99%
“…The voltage-gated channel Hv1, which is the sensor of electric voltage responsible for the alkalization of the intracellular environment necessary in the process of capacitation, hyperactivation, acrosomal response and sperm motility, seems to be most vulnerable to electromagnetic waves [15,16]. Based on the results of studies concerning the effect of electromagnetic waves on cells of the immune system, it is known that the effect of EMR modifies the transport of Ca ions to the cell, and the wave frequency close to 15 Hz exerts the strongest effect on this phenomenon [17].…”
Section: Mechanisms Of the Effect Of Emrmentioning
confidence: 99%
“…The first electrophysiological recording of voltage-dependent proton current in snail neurons were reported by Thomas and Meech [120]. Later studies, primarily done by DeCoursey group [121][122][123], found similar currents in other cell types [124]. However, controversy in the field on whether proton channels were in fact molecular entities had been present since 1989 after studies from Byerly and Suen [125].…”
Section: Discovery Of the Voltage-gated Proton Channel Hv1mentioning
confidence: 99%